2018
DOI: 10.1021/acs.est.8b04571
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Shorebird Migratory Fueling Physiology and Departure Timing in Relation to Polycyclic Aromatic Hydrocarbon Contamination in the Gulf of Mexico

Abstract: Shorebirds depend on staging sites in the Gulf of Mexico that are frequently subject to pollution by oil and its toxic constituents, polycyclic aromatic hydrocarbons (PAHs). It was hypothesized that PAH contamination lowers staging site quality for migratory shorebirds, with consequences for fueling and departure timing. Sediment total PAH concentrations were measured at six staging sites along the Texas and Louisiana Gulf Coast. Sites in Louisiana were expected to have higher total PAH concentrations as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…1). We classified trapping sites in the GOM into three staging areas: (1) North Padre Island, Texas; (2) Bolivar Flats, Texas; and (3) Louisiana (composed of Elmer's Island, Grand Isle, and Port Fourchon) based on evidence that individuals did not make local movements between these three areas (Bianchini and Morrissey 2018a).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…1). We classified trapping sites in the GOM into three staging areas: (1) North Padre Island, Texas; (2) Bolivar Flats, Texas; and (3) Louisiana (composed of Elmer's Island, Grand Isle, and Port Fourchon) based on evidence that individuals did not make local movements between these three areas (Bianchini and Morrissey 2018a).…”
Section: Study Areamentioning
confidence: 99%
“…New World Sanderling can migrate up to 10,000 km annually between their wintering grounds in South and Central America and the Gulf of Mexico (GOM) and their breeding grounds in the Canadian Arctic (Macwhirter et al 2020). We recently found that departure dates vary among Sanderling trapped in different staging sites in the GOM, which is linked to individual condition and oil spill contaminant levels (Bianchini and Morrissey 2018a). Here, we investigated whether these individuals from different GOM staging sites continue to show differences in arrival and subsequent departure timing as they migrate farther north.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most immediate impacts of oil are from physical contact or ingestion [ 15 ]; an estimated 600,000–800,000 birds were killed during the DWH spill [ 16 ]. Negative impacts on bird populations also result from long-term exposure to polycyclic aromatic hydrocarbons (PAHs) via multiple pathways [ 17 19 ], or from changes in habitat quality or resource availability due to oiling [ 4 , 13 ]. For example, following the Exxon Valdez spill in Alaska, Harlequin Duck ( Histrionicus histrionicus ) populations did not fully recover for at least 9 years post-spill [ 20 ], and experienced chronic exposure to oil for at least 20 years [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, demographic variables such as the proportion of nonbreeders and adult survival rates have been suggested to be severely affected by oil spills (Votier, Birkhead, et al., 2005 ; Votier, Hatchwell, et al., 2005 ; Wolfaardt et al., 2009 ). Finally, while several studies have focused on birds killed by oil pollution, fewer studies have examined the physiological and plumage consequences for individuals that survived oil spills (Alonso‐Alvarez et al., 2007 ; Bianchini & Morrissey, 2018 ; Champoux et al., 2020 ; Horak et al., 2017 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%